Answer:
when each side length of a cube increases by 1 unit, the volume increases by 3x² + 3x + 1 (units)³
Step-by-step explanation:
Let the initial length of the sides of the cube = x unit
when the length of the cube = x ; volume of the cube = length × breadth × height = x × x × x = x³ (unit)³
when the length increased by 1 unit,
new length = (x + 1) unit
New volume = (x + 1) × (x + 1) × (x + 1)
multiplying the first two brackets
New volume = (x² + 2x + 1 ) (x + 1)
espanding the brackets
New volume = x³ + 2x² + x + x² + 2x + 1
New volume = x³ + 3x² + 3x + 1 (unit)³
Change in volume:
(New volume) - (old volume)
(x³ + 3x² + 3x + 1) - (x³)
x³ + 3x² + 3x + 1 - x³
collecting like terms:
(x³ - x³) + 3x² + 3x + 1
0 + 3x² + 3x + 1
change in volume = 3x² + 3x + 1
Therefore, when each side length of a cube increases by 1 unit, the volume increases by 3x² + 3x + 1 (units)³